2020
DOI: 10.14203/j.baca.v41i1.585
|View full text |Cite
|
Sign up to set email alerts
|

Kolaborasi Peneliti Di Era Teknologi Informasi Dan Komunikasi

Abstract: Advances in information and communication technology have an impact on the increasing number of scientific publications in the world. Scientific papers are indicators of a country's progress in the academic field. One strategy used to improve the quality of research is to collaborate with researchers. There is not much research that addresses the collaboration of researchers. This article provides an overview of the cooperation of researchers including the background of the partnership, as well as aspects that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Students learn to convey ideas and perspectives to other students through the SFAE learning model. It is effective for training students to speak in order to express their own notions, voices, and beliefs (Amelia & Syahputra, 2019;Rusdi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students learn to convey ideas and perspectives to other students through the SFAE learning model. It is effective for training students to speak in order to express their own notions, voices, and beliefs (Amelia & Syahputra, 2019;Rusdi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Communication can be interpreted as a process of exchanging ideas, points of view or information between communicators and communicants. Judging from the process, communication is a social process to convey feelings or ideas with the intention of influencing others (Ngalimun, 2019;Rusdi et al, 2020). Thee results of observations and interviews conducted at SDIT Al Manar indicated that the learning outcomes and communication skills of students in thematic subjects were still very low.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini berpengaruh karena minimnya informasi yang mereka dapatkan. Terkadang mereka hanya menerima informasi dan materi hanya dari buku, sosmed ataupun website [4], yang ditemukan lewat searching di internet. Informasi yang tersedia dimedia-media tersebut kadang tidak lengkap dan memberikan informasi yang kurang menarik minat generasi milenial untuk dipelajari.…”
Section: Pendahuluanunclassified
“…The collaboration carried out only between ASEAN countries is defined as regional collaboration (Amelia, Nadhiroh, Rahmaida, Hardiyati, & Handayani, 2017). Research collaboration itself can be characterized as a form of collaboration carried out by one or two or more people (researchers) to achieve a common goal of producing a work (Arlianis, 2016) Author collaboration occurs due to several factors, which include first, personal factors, namely motivation, and interest in participating; second, professional factors, which involve experience and skills as well as the quality of research problems; the third factor is the factor of research organizations and collaboration of national and international organizations (Rusdi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%